2020
DOI: 10.1098/rsos.200066
|View full text |Cite
|
Sign up to set email alerts
|

Inner surface of Nepenthes slippery zone: ratchet effect of lunate cells causes anisotropic superhydrophobicity

Abstract: Inner surface of Nepenthes slippery zone shows anisotropic superhydrophobic wettability. Here, we investigate what factors cause the anisotropy via sliding angle measurement, morphology/structure observation and model analysis. Static contact angle of ultrapure-water droplet exhibits the value of 154.80°–156.83°, and sliding angle towards pitcher bottom and up is 2.82 ± 0.45° and 5.22 ± 0.28°, respectively. The slippery zone under investigation is covered by plenty of lunate cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For example, many surfaces of plants and animals exhibit superhydrophobic properties, such as lotus leaves, mussels, butterfly wings, water strider legs, and nepenthes. [1][2][3][4][5] These superhydrophobic phenomena have been thoroughly proven that the micron-sized papillary structures on the surface and waxy hydrophobic substances of the surfaces such as lotus leaf would cause the water droplets falling off the lotus leaf accompanied by carrying away dust or other substances, resulting in a self-cleaning effect. Based on the extensive exploration and analysis of this specific functional phenomenon from nature, German scientists, Barthlott et al first proposed the "lotus effect" in 1997, which was then considered as a special wetting property.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many surfaces of plants and animals exhibit superhydrophobic properties, such as lotus leaves, mussels, butterfly wings, water strider legs, and nepenthes. [1][2][3][4][5] These superhydrophobic phenomena have been thoroughly proven that the micron-sized papillary structures on the surface and waxy hydrophobic substances of the surfaces such as lotus leaf would cause the water droplets falling off the lotus leaf accompanied by carrying away dust or other substances, resulting in a self-cleaning effect. Based on the extensive exploration and analysis of this specific functional phenomenon from nature, German scientists, Barthlott et al first proposed the "lotus effect" in 1997, which was then considered as a special wetting property.…”
Section: Introductionmentioning
confidence: 99%
“…Here it is worth noting that some experimental studies suggested that such a transition was plausible. 33,34 For example, for hydrophilic materials with an intrinsic contact angle of 70 , a transition from noncomposite to composite states could occur if the depth of surface topography pores (a similar parameter to the pillar height) was very large. This happens perhaps because the difference in free energy and barrier between the noncomposite to composite states was so small due to adequate roughness that the transition between the two states could be easily realized under the experimental conditions where external resources may be available.…”
Section: Comparisons Of Free Energy and Free Energy Barriers Between Noncomposite And Composite Statesmentioning
confidence: 99%
“…A biological example of this has been observed on pitcher plants 47 , where crescent shaped cells provide a similar topography which makes escape for its victims even more difficult than usual. Butterflies too have been observed to sometimes have a directionality of wetting 48 .…”
Section: Directional Wettingmentioning
confidence: 99%